2023
DOI: 10.2196/43263
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Experiences of Engaging in a Psychological Flexibility Skill Training App for Burnout and Well-being: Pilot Feasibility Study

Abstract: Background Medical students are at higher risk of burnout than the general population. Interventions that facilitate adaptive coping behaviors (eg, Psychological Flexibility) in the context of inherent stressors associated with medical training could mitigate burnout risk and improve well-being. Delivering these interventions using smartphone apps offers advantages such as accessibility, scalability, mitigation of time and stigma barriers, and facilitation of individual tailoring (individualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…Increasing teacher interaction to support them in understanding the cumulative knowledge building in the curriculum could also benefit the students. In addition to improving the learning environment, the interventions could also be targeted to enhance the students' psychological flexibility ( 51 , 52 ), which in working life has been shown to mitigate burnout ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing teacher interaction to support them in understanding the cumulative knowledge building in the curriculum could also benefit the students. In addition to improving the learning environment, the interventions could also be targeted to enhance the students' psychological flexibility ( 51 , 52 ), which in working life has been shown to mitigate burnout ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…This provided students with the opportunity to participate in the study during the semester while reducing participation burden by ensuring that the timing of outcome measures did not correspond with critical assessment periods. This duration was considered appropriate as Levin et al [ 75 ] observed intervention effects for a similar 4-week program, and feasibility trialing of the current app demonstrated that medical students engaged most frequently during the early weeks of access [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…The version of BiSi implemented in this study incorporated medical student feedback from a small feasibility trial of the app [ 68 ] with the aim of enhancing intervention relevance and engagement. This included clear explanations of what to expect during each stage of the intervention, providing progress indicators for all app components, providing earlier opportunities for personally relevant experiential learning and self-reflection (during stage 1), and delivering content in both written and audio formats where practical (during stage 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation